Pharmacokinetics and Safety of Doripenem in Healthy Chinese Subjects and Monte Carlo Dosing Simulations - Yu Wang; Xiaofen Liu; Kun Li; Yaxin Fan; Jicheng Yu; Hailan Wu; Yi Li; Xiaojie Wu; Beining Guo; Xin Li; Jiali Hu; Jufang Wu; et al. (Antibiotics, 2022)
The aim of this study was to investigate the pharmacokinetics (PK) of doripenem in healthy Chinese subjects and evaluate the optimal dosage regimens of doripenem. A randomized, single-dose, three-period, self-crossover controlled extended-infusion clinical trial was conducted with 12 healthy Chinese subjects. Plasma and urine samples were collected to determine doripenem concentrations. Non-compartmental and population PK analysis were performed to characterize the PK of doripenem. The Monte Carlo simulation was employed to optimize dosing regimens based on the probability of target attainment of doripenem against pathogens with different minimum inhibitory concentrations (MIC). All 12 healthy Chinese subjects completed the study, and the doripenem was well tolerated. The study showed linearity relationships in the peak plasma concentration and the area under the concentration-time curve after intravenous infusion of doripenem from 0.25 g to 1.0 g. The cumulative urinary recovery rate of doripenem was 68.1–72.0% within 24 h. PPK modeling showed a two-compartmental model, with first-order elimination presenting the best fit for doripenem PK. Monte Carlo simulation results showed that 1.0 g q12h or 0.5 g q8h was an optimal regimen for pathogens susceptible to doripenem (MIC ≤ 1 mg/L); while high dose and extended infusion (1 g, q8h, 4 h infusion) was proposed for unsusceptible pathogens (2 ≤ MIC ≤ 8 mg/L). In the dose range of 0.25 to 1.0 g, doripenem showed linear pharmacokinetics. Doripenem at 1.0 g with a prolonged infusion time of 4 h was predicted to be effective against pathogens with MICs as high as 8 mg/L.